Roots of 'Program' Revisited: Considering the fundamental nature and malleability of programming. - De Mol, Liesbeth; Bullynck, Maarten (Communications of the ACM, 2021)
The article discusses the history of the "stored program":in computer science since John von Neumann's 1945 description of the EDVAC mainframe computer. The etymological origins of "program" in the radio broadcasting industry and "program clocks" which scheduled factory production are examined along with the alleged importance of establishing a narrative history of computing.